Blunt and Non-Blunt Cannabis Use and Risk of Subsequent Combustible Tobacco Product Use Among Adolescents. Issue 8 (7th December 2019) - Mayer, Margaret E; Kong, Grace; Barrington-Trimis, Jessica L; McConnell, Rob; Leventhal, Adam M; Krishnan-Sarin, Suchitra
Abstract: Introduction: Cannabis—including blunts (cannabis rolled in tobacco-containing cigar casing) —is commonly the first substance used among adolescents and may increase the likelihood of subsequent initiation of combustible tobacco products. Aims and Methods: Data were pooled from two prospective studies of adolescents in California and Connecticut (total N = 4594). Logistic regression models assessed the association of baseline ever blunt use and ever non-blunt cannabis use (vs. never cannabis use) with subsequent initiation of any combustible tobacco-only product (ie, cigarettes, cigars, or cigarillos) by 1-year follow-up after adjustment for demographic characteristics and other tobacco product use at baseline. We also assessed whether estimates differed by prior e-cigarette or hookah use at baseline. Results: Among never combustible tobacco-only product users ( N = 2973), 221 (7.4%) had ever used a blunt and 114 (3.8%) had ever used only non-blunt cannabis at baseline. Blunt use (adjusted odds ratio [AOR] = 1.98, 95% confidence interval [CI]: 1.30 to 3.01) and non-blunt cannabis use (AOR = 2.38, 95% CI: 1.41 to 4.00) were independently associated with greater odds of combustible tobacco-only product initiation by follow-up. Among those who had not tried e-cigarettes or who had not tried hookah, blunt use and non-blunt cannabis use were associated with significantly increased odds of combustible tobacco product initiation; among those who had tried e-cigarettes or hookah, the association was not significant. Conclusions: We found blunt and non-blunt cannabis use to be associated with subsequent combustible tobacco-only product initiation, particularly among adolescents who had not also tried other products containing nicotine. Implications: Adolescent-focused tobacco prevention efforts should consider incorporating cannabis products, including blunts. More research is needed to understand how blunt use and cannabis use more broadly are associated with initiation of tobacco products.